FAST-TRACK SAFETY CULTURE INTO BUSINESS CULTURE AND STOP INCIDENTS/LOSSES: INDIA CASE STUDY - Lal, Harbans (International Journal of Research -GRANTHAALAYAH, 2022)
Safety culture is what we call as people’s safe behaviours. Safety culture is a fast growing wave in industry today. Addressing gaps in building longterm supportive safety culture for companies underlines a set of unresolved questions on behavioural risks management in industry and possible solutions. Everyone raises voice for safety, safety culture comes and risk disappears, is it so simple? Most companies delayed their HSE decisions till they suffered. Why so? Without inculcating safety as a core corporate value, industry can not be considered safe. Behavioural safety culture is a live surveillance on the risks and their spot-correction to ensure that the safety culture building process is kept on. Behaviouralisation of safety culture is necessary to overcome incidents and accidents at sites. Behavioural Safety education to one and all is the safety culture being addressed by the most. Ideologies on safety cultures vary across the industries in terms of practices. The present article dwelt on identifying the unresolved critical questions on behavioural safety supportive culture implementation in industry and raised possible solutions. The data were collected from 603 industry professionals as being study participants. The sampling method was a non-random convenience sampling. A set of ten themes of research findings reflected upon the critical issues such as basic questions on longterm safety cultures; Reactive safety culture; collective voice and leadership for at-risk behaviours; Religion, spirituality, festivities for safety at sites; Implementation of safety with feeling for others; Features of companies not empowering their workforce for performing safety implementation; Competencies gap amongst the safety professionals, the major roadblocks in HSE decisions-making, the spot-implementation of behavior based safety (BBS) approach by top leaders, and myriad factors to advance the success of longterm supportive safety culture. Fast-tracking supportive safety culture at sites would mean the next levels of hard work. The news of any safety incident travels to the share holders and impact the company’s share price. The professionals reminded to strengthen safety culture in business cultures with full behavioral safety implementation alongwith daily reviews. This paper has added an in-depth sense of qualitative data on the topic.